(untitled) (Bangladesh Journal of Zoology, 2015)
Bacterial and nutritional quality of fresh and salted hilsa collected from four markets of Dhaka city were investigated. Five different culture media viz. nutrient agar, EMB agar for coliform, SS agar for Salmonella-Shigella, MSA agar for Staphylococcus and TCBS for Vibrio were used. The highest heterotrophic bacterial count 1.22 ± 0.12 × 106 cfu/g was recorded in the fresh fish sample of Karwan Bazar. Maximum coliform count, 1.20 ± 0.10 × 106 cfu/g was detected in the fresh fish sample of the same market. No bacterial colony was found on SS agar and TCBS agar plate in salted fish. Proximate composition of raw hilsa of dorsal and ventral part was 56.49 ± 0.13% and 55.45 ± 0.06% moisture, 23.62 ± 0.28% and 22.99 ± 0.36% protein, 18.01 ± 0.39% and 18.96 ± 0.43% fat and 1.71 ± 0.04% and 2.26 ± 0.09% ash, respectively. In salted T. ilisha, the proximate composition of dorsal and ventral part was 45.13 ± 0.54% and 40.20±0.20% moisture, 20.79 ± 0.17% and 21.48 ± 0.15% protein, 16.89 ± 0.47% and 19.54 ± 0.26% lipid and 16.65 ± 0.41% and 18.35 ± 0.08% ash. The fresh fish samples were associated with high bacterial loads than that of salted fish. The protein, lipid, moisture contents decreased and ash content increased after salting condition. Bangladesh J. Zool. 42(2): 227-236, 2014